2021
DOI: 10.22336/rjo.2021.58
|View full text |Cite
|
Sign up to set email alerts
|

Treating corneal neovascularization using a combination of anti-VEGF injection and argon laser photocoagulation application - case report

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Both lasers can treat efferent NV because these vessels have relatively slower blood flow but can be ineffective against thinner afferent vessels with faster blood flow [8]. Numerous case reports have reported outcomes of argon laser in combination with anti-VEGF treatment such as bevacizumab, all of which described short-term regression of corneal NV (Figure 5, Supplemental Digital Content, http://links.lww.com/COOP/A66) [11,74,75]. A study by Kumar et al examined 40 corneal NV eyes treated by Nd: YAG laser and reported a statistically significant difference in the percentage of mean NVA three months posttreatment [76].…”
Section: Laser Therapiesmentioning
confidence: 99%
“…Both lasers can treat efferent NV because these vessels have relatively slower blood flow but can be ineffective against thinner afferent vessels with faster blood flow [8]. Numerous case reports have reported outcomes of argon laser in combination with anti-VEGF treatment such as bevacizumab, all of which described short-term regression of corneal NV (Figure 5, Supplemental Digital Content, http://links.lww.com/COOP/A66) [11,74,75]. A study by Kumar et al examined 40 corneal NV eyes treated by Nd: YAG laser and reported a statistically significant difference in the percentage of mean NVA three months posttreatment [76].…”
Section: Laser Therapiesmentioning
confidence: 99%
“…Contrastingly, it is difficult to obliterate afferent vessels as they are thinner, more deeply located in the cornea, and characterized by a rapid blood flow. In this case, laser therapy is ineffective, and thermal damage due to repeated use might promote neovascularization recurrence [168,169]. The complications of laser therapy can include corneal endothelial damage, corneal thinning, intraocular hemorrhage, pupillary displacement, iris atrophy, and corneal suture lysis after corneal transplantation [2].…”
Section: Laser Therapymentioning
confidence: 99%
“…In contrast, it is difficult to obliterate afferent vessels because they are thinner and more deeply located in the cornea and are characterized by rapid blood flow. In their case, laser therapy is ineffective, and when repeated, thermal damage may promote the recurrence of neovascularization [62,63].Complications of laser therapy can include corneal endothelial damage, corneal thinning, intraocular hemorrhage, pupillary displacement, iris atrophy, and corneal suture lysis after corneal transplantation [2].…”
Section: Laser Therapymentioning
confidence: 99%